Klebsiella pneumoniae under xylose pressure: the growth adaptation, antimicrobial susceptibility, global proteomics analysis and role of XylA and XylB proteins - Ruolan Yi; Jiaoyang Zheng; Zhichao Xu; Jiayan Wu; Fangfang Liu; Jinxin Zheng; Duoyun Li; Shiqing Han; Zhijian Yu (BMC Microbiology)
Abstract Klebsiella pneumoniae can be cultured in medium with xylose as the sole carbon source. However, the effect of xylose exposure on its growth adaptation, virulence, antimicrobial susceptibility, and proteomic response remain unclear. Here, we show that low concentrations of xylose (≤ 2%) promote the planktonic growth of three K. pneumoniae isolates (K2044, EKP19, and EKP108) in a concentration-dependent manner, while 8% xylose consistently inhibits their planktonic growth. Notably, the xylose-induced isolate K2044−8Xyl−60G, when exposed to various xylose concentrations, exhibited the longest logarithmic growth phase and the highest optical density (OD) after logarithmic growth, compared to K2044. In contrast, the xylose-induced isolates EKP19 and EKP108 did not successfully reshape growth adaptation under persistent xylose pressure compared to K2044. Additionally, while the growth adaptation of K2044−8Xyl−60G under xylose pressure was confirmed, no amino acid mutations were detected in the functional proteins of this xylose-induced isolate, suggesting that persistent xylose pressure does not cause nonsense mutations in the bacterial genome. Xylose exposure reduced the gentamicin minimum inhibitory concentration (MIC) in all three K. pneumoniae isolates (K2044, EKP108, and EKP19) and their xylose-induced derivatives. In a Galleria mellonella infection model, significantly decreased virulence was observed in the xylose-induced isolates of K2044 and EKP19. Proteomic analysis of K2044−8Xyl−60G treated with 8% xylose revealed upregulation of proteins involved in glycolysis, the pentose phosphate pathway, and transmembrane transport. We also constructed K2044-ΔxylA (with deletion of the xylA gene) and K2044-ΔxylB (with deletion of the xylB gene). Our data showed that K2044-ΔxylA exhibited enhanced planktonic growth compared to K2044 when exposed to xylose concentrations of ≥ 4%, while K2044-ΔxylB displayed significantly reduced growth capacity regardless of xylose exposure. The virulence of K2044-ΔxylA was also significantly reduced, as demonstrated by the increased survival rates in G. mellonella infection models. Additionally, xylose exposure strongly enhanced membrane depolarization in both K2044-ΔxylA and K2044-ΔxylB compared to the wild-type K2044. Proteomic analysis indicated that the deletion of xylA primarily affected functional proteins related to ribosomes, xylose transmembrane transporters and capsular polysaccharides, while the deletion of xylB impacted the expression of xylose metabolism-related proteins. In conclusion, xylose exposure can reshape the growth adaptation, virulence, and antimicrobial susceptibility of K. pneumoniae in an isolate-specific manner, with xylA playing a more critical role than xylB under high xylose concentrations.